Commentary on N. Ghaemi's “Hippocratic Psychopharmacology of Bipolar Disorder” Maintenance Treatment in Bipolar Disorder - Tohen, Mauricio (Matrix Medical Communications, 2006)
Bipolar disorder is a chronic recurring condition that is associated with high mortality and severe functional and psychosocial impairments. Treatment strategies that prolong recovery from a mood episode and delay relapse into a new mood episode are essential for long-term improvements in outcomes. Maintenance treatments for bipolar disorder should be evaluated on the strength of the empirical evidence and with the recognition that some treatments may be more effective in preventing relapse into manic, depressive, or mixed episodes.